Medieval fortifications in Cilica - Vandekerckhove, Dweezil, author.
1 online resource.
Keywords: In Medieval Fortifications in Cilicia Dweezil Vandekerckhove offers an account of the origins, development and spatial distribution of fortified sites in the Armenian Kingdom (1198-1375). Despite the abundance of archaeological remains, the Armenian heritage had previously not been closely studied. However, through the examination of known and newly identified castles, this work has now increased the number of sites and features associated with the Armenian Kingdom. By the construction of numerous powerful castles, the Armenians succeeded in establishing an independent kingdom, which lasted until the Mamluk conquest in 1375. Dweezil Vandekerckhove convincingly proves that the medieval castles in Cilicia are of outstanding architectural interest, with a significant place in the history of military architecture.